Social distance and intergroup contact: German university students' views on islam and muslims - Ata, Abe W. (Interreligious studies and intercultural theology, 2022)
The effects of intergroup contact in reducing prejudices have been well documented, but few studies have investigated the importance of the broader context within which contact occurs. This article examines the predictors of social distance from Muslims in a large sample of (non-Muslim) German university students (N = 404). Intergroup contact was an important predictor of reduced social distance even after demographics and perceptions of parents, tertiary institutions, media and broader intergroup dynamics were taken into account. The contact-social distance relationship was, however, mediated in part by perceived parental support for intergroup relations and perceived fairness of media representation. Students’ perceptions of broader group dynamics relating to assigning positive and negative attributes largely impeded the relationship - more so for male students than female. The findings attest to the importance of the broader context within which contact occurs. Having contact with outgroup members leads to reduced social distance from the outgroup, but perceived norms and outgroup perceptions play a pivotal role in explaining this relationship.